The effect of cognitive-behavioral counseling on anxiety in the mothers of infants in the NICU: A randomized controlled trial - Koochaki, Massumeh (F1000Res, 2017)
Background: Pressures and tensions in everyone’s life can cause a wide range of mental disorders such as anxiety. One of these tensions is the birth of a baby who requires special care, which can cause personal and social problems for the mother if no appropriate measures are taken to help them. The present study was conducted to determine the effect of cognitive-behavioral counseling on anxiety in the mothers of infants in the Neonatal Intensive Care Unit. Methods: This randomized controlled trial recruited 90 women presenting to Kowsar Hospital in Qazvin in 2016. They were enrolled by convenience sampling and randomly assigned to control and intervention groups. Eight sessions were held for each group. Beck Anxiety Inventory was filled by mothers at the beginning of intervention, at the end of the eighth session and three weeks after the intervention. The data was analyzed by generalized estimating equations (GEE) method. Results: According to the results, maternal anxiety showed no significant differences between the two groups before intervention (p = 0.408 and p = 0.881). Based on GEE test, the mean score of anxiety was significantly different in the two groups (p = 0.026) immediately and three weeks after the intervention in that it was lower in the intervention group. Friedman test results also confirmed the reducing trend of mean score of anxiety in the three stages (p = 0.000). Conclusions: Counseling has a positive effect on reducing the anxiety of mothers of children with special needs, therefore it can be used to improve their condition.